The Impact of Corporate Governance on Financial Decision-making: Evidence from Non-financial Institutions in the Australian Securities Exchange - Leviticus Mensah,; Richard Arhinful,; Murad Abdurahman Bein , (Asian Academy of Management Journal of Accounting and Finance, 2024)
The objective of this study was to examine the impact of corporate governance on the financial choices of non-financial companies operating in the Australian Securities Exchange. A purposive sampling technique was employed to select a total of 113 firms representing 14 sectors listed in the Australian Securities Exchange during the period from 2008 to 2021. The findings of the study revealed a positive and significant relationship between the size of the board, gender diversity among board members, board member affiliation and board compensation with the financial decisions of the corporations. Additionally, the study identified that the presence of experienced and non-executive board members had a negative and significant impact on internally generated funding. Furthermore, it was observed that board gender diversity, board size, board member affiliation and board compensation displayed a positive and significant association with debt financing, internally generated financing and equity financing. Most organisations displayed a preference for internal and debt financing over equity funding. Aligning governance with financial decisions enhances firms’ cost of capital. Governance quality affects capital market access, debt and equity costs. Effective governance leads to favourable financing terms.